Joining of silicon carbide ceramics using a silicon carbide tape. Issue 4 (20th February 2019) - Kim, Yong‐Hyeon; Jang, Seung Hoon; Kim, Young‐Wook
Abstract: This paper reports the joining of liquid‐phase sintered SiC ceramics using a thin SiC tape with the same composition as base SiC material. The base SiC ceramics were fabricated by hot pressing of submicron SiC powders with 4 wt% Al2 O3 –Y2 O3 –MgO additives. The base SiC ceramics were joined by hot‐pressing at 1800‐1900°C under a pressure of 10 or 20 MPa in an argon atmosphere. The effects of sintering temperature and pressure were examined carefully in terms of microstructure and strength of the joined samples. The flexural strength of the SiC ceramic which was joined at 1850°C under 20 MPa, was 343 ± 53 MPa, higher than the SiC material (289 ± 53 MPa). The joined SiC ceramics showed no residual stress built up near the joining layer, which was evidenced by indentation cracks with almost the same lengths in four directions.